TINGKAT RESIKO JATUH PADA LANSIA YANG MENGALAMI HIPERTENSI - Mustriwi Mustriwi; Meitha Tibyana Furqi; Apriyani Puji Hastuti (Jurnal Kesehatan Hesti Wira Sakti, 2023)
Introduction: Hypertension in the elderly is caused by decreased arterial elasticity so that blood pressure tends to increase. Hypertension cannot be ignored, because it can cause damage to the blood vessels in the heart. Damage to the heart's blood vessels will result in blood flow to the heart muscles being obstructed. Increasing age, especially in the elderly who often do physical activity. The author conducted this study aiming to describe the level of risk of falling in the elderly who have hypertension. Methods: This research uses a descriptive method in the form of a case study. The population of this study were all elderly people with hypertension in Lumbangsari Village, Bululawang District, Malang Regency as many as 116 elderly, 56 elderly had moderate hypertension, 40 elderly had mild hypertension and 20 other elderly had prehypertension. The sampling technique used was accidental sampling with a sample size of 116 respondents. The research instrument was the MFS (Morse fall scale) with univariate data analysis using a frequency distribution. Results: Based on the results of the research that has been conducted regarding the description of the level of risk of falling in elderly hypertensives that the elderly who have fallen, the results show that most of the 56 respondents (48.3%) have a high risk of falling, a small proportion of 32 respondents (27.6%) have a moderate risk of falling and a small portion of 28 respondents (24.1%) did not have a risk of falling. This is influenced by several factors, namely age, gender, education, occupation, income, disease, smoking, excessive salt consumption. Conclusion: Based on this research, it is hoped that it can motivate residents, especially the elderly, to better maintain their diet and always maintain safety and health as well as the risks that may be experienced, especially by the elderly.